Exploring the impact of perceived risk and trust on tourist acceptance intentions in the post-COVID-19 era: A case study of Hainan residents - Zhou, Hongxia; Ibrahim, Johan Afendi Bin; Mohamed, Ahmad Edwin Bin (Frontiers in Psychology, 2022)
Hainan, is the only free trade port that also exudes quintessence of the culture of China. Tourism is one of Hainan's most lucrative industries. On the one hand, the regional economy is flourishing and on the other hand, the economy is facing unprecedented impacts from the COVID-19 pandemic. In response to the affected global market environment, this study investigates Hainan residents' acceptance intentions, or tolerance, of tourists. Here, based on the theory of reasoned action, which includes “subjective norm” combined with “trust,” “perceived risk,” and “perceived value.” Using “resident attitude” as a mediator, theoretical research frameworks were developed. A total of 447 valid responses were collected using online and paper-copy questionnaires distributed to Hainan residents from 15 July 2021 to 10 November 2021. The data from the questionnaires were used for three analyses namely, descriptive statistical analysis, measurement model verification, and structural equation modeling analysis. Findings show a positive effect of trust on residents' attitudes in Hainan; perceived value and subjective norm showed a positive effect on resident acceptance intentions for tourism; the perceived risk of residents showed a more negative effect on attitudes toward tourists, but the influence was small. Finally, through the results of the study, theoretical and practical implications in a post-pandemic era are discussed.